Service Excellence dalam Meningkatkan Loyalitas Nasabah: Peran Mediasi Kepuasan pada Bank NTB Syariah - Putri Azzahroh, Evrita (Kartika: Jurnal Studi Keislaman, 2025)
This study aims to analyze the effect of service excellence on customer loyalty with customer satisfaction as a mediating variable at Bank NTB Syariah. The research background is based on the significant growth of Bank NTB Syariah over the last five years, as reflected in the increase of assets, customer base, and financing, which serve as the pillars of the bank’s development. A quantitative correlational approach was employed to examine the relationship among variables without manipulation. The sample consisted of 100 respondents, determined through accidental sampling using Slovin’s formula. Data were collected using a structured questionnaire with a rating scale and analyzed with Partial Least Square (PLS). The results indicate that service excellence has a positive and significant effect on customer satisfaction, and customer satisfaction mediates the relationship between service excellence and customer loyalty. These findings reinforce the theory that customer loyalty does not emerge instantly but requires superior service strategies and sustainable satisfaction.